2007
DOI: 10.1002/anie.200604306
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Metal–Organic Frameworks (MOFs) Based on Indium‐Trimer Building Blocks: A Porous MOF with soc Topology and High Hydrogen Storage

Abstract: The potential of the molecular-building-block (MBB) approach for the assembly and development of functional solid-state porous materials has already been recognized. [1] This approach offers a prospective avenue toward the design and construction of novel materials; that is, desired properties can be incorporated at the design stage. These properties are required to address the myriad technological challenges that face us, including hydrogen storage for fuel applications. In metal-ligand directed assembly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
360
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 651 publications
(384 citation statements)
references
References 58 publications
22
360
1
1
Order By: Relevance
“…N 2 physisorption at 77 K, TGA and XRD confirmed the presence of MIL-68 [21][22][23] , MIL-88A [24][25][26] , MIL-100 [27][28][29] , MIL-101 [30][31][32] , and MIL-127 [33][34][35] (see Table S1, Figure S1 and Figure S2) ‡. XRD of the F300 Fe-BTC MOF revealed a very low degree of crystallinity, but the MIL-100 topology was confirmed since the isotherm contained an additional step in the micropore regime corresponding to the large cages in the MTN-type framework [27][28] .…”
Section: Characterization Of Mof Precursorsmentioning
confidence: 86%
“…N 2 physisorption at 77 K, TGA and XRD confirmed the presence of MIL-68 [21][22][23] , MIL-88A [24][25][26] , MIL-100 [27][28][29] , MIL-101 [30][31][32] , and MIL-127 [33][34][35] (see Table S1, Figure S1 and Figure S2) ‡. XRD of the F300 Fe-BTC MOF revealed a very low degree of crystallinity, but the MIL-100 topology was confirmed since the isotherm contained an additional step in the micropore regime corresponding to the large cages in the MTN-type framework [27][28] .…”
Section: Characterization Of Mof Precursorsmentioning
confidence: 86%
“…In order to enhance the H 2 binding energy in these materials, strategies such as the formation of very narrow pores [14,15,17] (in which overlapping potentials from two or more pore walls increases the binding energy between the H 2 and the framework), framework catenation/interpenetration [18] and doping of frameworks with light electron-donating non-transition-metal centres to increase H 2 uptake [19] have been undertaken. In particular, access to exposed metal sites can increase the affinity of H 2 through direct coordination to metal centres.…”
mentioning
confidence: 99%
“…11 To address this issue, we focused our attention to other iron(III)-carboxylate based MOFs (Figure 1) that not only possess the same building units as the MIL-88 series, and thus large amounts of Lewis acid sites, but also rigid frameworks with larger windows/pores, namely, MIL-100 (Cr, Fe) 13 and MIL-127(Fe) 14 (analogous to soc-MOF(In) 15 ). MIL-100 possesses two types of mesoporous cages (d ∼ 24 and 29 Å, respectively), accessible through microporous pentagonal and hexagonal windows, while MIL-127(Fe) exhibits a 3D microporous system (d ∼ 5-7 Å) with both hydrophobic and hydrophilic features 15 ( Figure 1). It has previously been shown that these particular MOFs easily adsorb or separate various types of gas molecules and their ability to coordinate polar or quadrupolar molecules (water, alcohols, C3, etc.)…”
mentioning
confidence: 99%